ANALISIS PRODUKSI BAWANG MERAH DI DESA LARANGAN KECAMATAN LARANGAN KABUPATEN BREBES - Basia, Lusmino; Nuryana Putri, Raha Dewi Sinta; Sukarniati, Lestari (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
Onion productivity in Indonesia is still low with an average of 9.24 tons/ha of national shallot productivity, far below the production potential of above 20 tons/ha. BPS data on horticultural crops tends to continue to increase the formation of GDP. This study aims to identify the factors influencing the production of shallot farmers in Larangan Village, Larangan District, Brebes Regency. The variables used in this study include independent variables such as capital, seeds, land area, fertilizers, pesticides, and labor, while the dependent variable is shallot production. This research employs a quantitative method. The data used in this study are primary data, collected through questionnaires distributed to shallot farmers in Larangan Village who were selected as samples. The study involved a sample of 70 shallot farmers. The data were processed using Eviews 12 with the multiple linear regression method. The results of this study indicate that capital, seeds, land area, fertilizers, and pesticides have a positive and significant partial effect on shallot production, whereas labor has no effect on shallot production.